Depression, anxiety and eating disorder-related impairment: moderators in female adolescents and young adults - Stadler, Johanna; Moessner, Markus; Bauer, Stephanie (International journal of environmental research and public health, 2021)
Adolescents and young adults, particularly females, are highly vulnerable to the development of anxiety disorders, depression, and eating disorders. Comorbid anxiety disorder or depression in eating disorders are associated with greater symptom severity, poorer prognosis, and burden of illness. Nonetheless, studies on what affects the relationship between anxiety, depression, and eating disorders in female at-risk samples are scarce. Using hierarchical linear modeling, the present study examined potential moderators to explain between-person differences in the association between anxiety, depression, and eating disorder-related impairment within 12- to 25-year-old females (N = 320). High impairment in anxiety/depression was associated with more severe eating disorder symptoms. Older age as well as greater impairment in mood dysregulation, self-esteem, and perfectionism were linked to more severe eating disorder symptomatology. Whereas mood dysregulation, self-esteem, and perfectionism had no statistically significant moderating effects, younger age appeared to augment the association of anxiety/depression and eating disorder symptomatology. Preventive care in particular needs to consider age-related effects as eating disorder symptoms are associated more strongly with symptoms of anxiety and depression in early adolescence.